The Contribution of Bugis' Traditional Games in Strengthening Students' Character Education at Madrasa - Suhra, Sarifa; Djubaedi, Dedi; Haji Mail, Awg Asbol Bin (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2020)
Bugis' traditional game originated from a folklore which is usually played by the society including children in Bone. It examines specifically mappasajang traditional game, its character value promotion and its contribution in strengthening students' character education at madrasa. This study was qualitative and took place at Madrasah Ibtidaiyah Amir al-Jannah Tippulue, Bone Regency. Primary data of this study were obtained from field observations and interviews with educational and community leaders. Secondary data were obtained from books and journals related to Bugis traditional games. Observation, interviews, and documentation were applied to gain the data. Qualitative data analysis was performed using interactive model analysis techniques. Triangulation was applied to test the validity of the data. The results showed that mappasajang traditional game could be played by both male and female madrasa students. This traditional Bugis game is full of character values. The traditional game contributed to strengthening students' character education at madrasa. This can be seen in various aspects of community life, such as in the fields of education, social, economy, and health.